Op getoonde foto optreden in het kader van de campagne. In het middel v.l.n.r. : Kosterman, Labij, ?, ?, Van Bladel (1977)
Op getoonde foto optreden in het kader van de campagne. In het middel v.l.n.r. : Kosterman, Labij, ?, ?, Van Bladel.